Are adult amateur musicians at 'high risk' of experiencing musculoskeletal symptoms?. Issue 1 (1st May 2020) - Stanhope, Jessica; Cook, Angus; Weinstein, Philip
Musculoskeletal symptoms (MSSs) are a common problem for musicians, but the MSS burden of amateur musicians specifically is under-investigated. For the first time we sought to compare the MSS prevalence and profile (e.g. MSS location, impact) of adult amateur musicians with those of non-musicians. Amateur and non-musicians were asked to complete a questionnaire that collected data on their demographics, musical activities and MSS outcomes. A total of 456 participants were included, 30.9% of whom were amateur musicians. MSSs were common for both amateurs and non-musicians (96.4% and 96.1%, respectively, for the last twelve months). The only significant difference between the two groups was for the twelve-month prevalence of head MSSs with amateur musicians having a higher prevalence than non-musicians (49.6% and 39.8%, respectively, p<0.05). We conclude that amateur musicians do not have a substantially different MSS prevalence and profile compared with non-musicians for this university-based population.